MUNCA NOASTRĂ-I TEATRU, IAR TOT CE FACEM E SPECTACOL - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
The theatre is no stranger to the library, it’s from the same area – culture. The connection with the theatre refers to the librarians work, library activity in general, because any action of the librarian and the library contributes to the experience putting on Municipal Library stage: headquarters, branches, departments, services... The author brings relevant examples of the Municipal Library „B.P. Hasdeu" activity, on each component of this concept, demonstrating that terms like theater production, performance, method, role, screenplay and a number of other terms are very familiar to librarians and library and are naturalized in domain vocabulary. When the theater is an operational library model, says the author, even the most ordinary tasks can conquer users, and any work directly observed by a user should be recognized as a theatre act. Now the libraries should more than once, to capture users. The show must go! The theatre is made of creative, talented librarians, which plays theirs role with passion, giving memorable performances!